Analisis Fenomena Dispensasi Kawin di Pengadilan Agama Lebong - Sab, Waas (Berasan: Journal of Islamic Civil Law, 2024)
The main problem in this study is the increase in the number of marriage dispensation applications from 2019-2021 after the birth of Law No. 16 of 2019. The purpose of this study is to find out the causal factors and the basis of consideration used by the judge in granting the application for marriage dispensation at the Lebong Religious Court. This type of research research is field research. The sources of data for this research are: 1) primary data, the results of interviews with judges at the Lebong Religious Court, especially judges who handle marriage dispensation cases; 2) secondary data, including official documents, books, research results in the form of reports and so on, the secondary data source in this study is the case of the marriage dispensation application being granted. After the data is obtained, it is then processed and analyzed with steps in the form of data reduction, data presentation and verification or drawing conclusions. Based on the results of the research while at the Lebong Religious Court, there are 5 factors that cause the increase in the submission of marriage dispensation applications, namely: (1) Factors affecting the amendment of Law no. 16 of 2019, (2) pregnancy factors, (3) education factors, (4) economic factors, and (5) factors that desire children to get married at an early age. Then the basis of the judge's consideration in granting the application for marriage dispensation at the Lebong Religious Court is: (1) there is an urgent reason that is urgent in nature such as the bride-to-be is pregnant, (2) the intention of the applicants, the judge will see the intention of the applicant, which is not only from tahsiniyat but must be zero darruriyat, (3) the completeness of administrative requirements, (4) the statements of children and witnesses,Â  (5) the physical and mental maturity of the child and, (6) the two prospective brides do not have a relationship that prohibits them from marrying.